وفرة وتنوع القشريات متفرعة القرون Cladocera في جنوب هور الحمار - عجيل, شاكر غالب; عباس, محمد فارس (Latakia University Journal -Biological Sciences Series, 2013)
جمعت عينات الهائمات الحيوانية فصليا من ثلاث محطات جنوب هور الحمار الواقع جنوب العراق خلال الفترة من كانون الثاني إلى كانون الأول 2011 ، بواسطة شبكة الهائمات ذات فتحات 0.90 ملم. تراوحت كثافة متفرعة اللوامس بين 79 فرد/م3 في المحطة الأولى (المسحب) خلال فصل الشتاء إلى 41971 فرد/م3 في المحطة الثانية (حرير) خلال فصل الربيع. كثافة متفرعة اللوامس في محطات الدراسة كانت مرتبطة طرديا مع درجة حرارة الماء وبدرجة اقل مع الملوحة. تم تسجيل 13 نوعاً من متفرعة اللوامس تعود إلى 11 جنساً في محطات الدراسة. سجلت قيم التنوع خلال فصل الشتاء في المحطات الثلاثة (1.68, 1.16, 1.68 على التوالي) بينما القيم الأدنى سجلت خلال فصل الربيع (0.06, 0.03, 0.01 على التوالي). Zooplankton samples were collected seasonally from three stations in the south of Al-Hammar Marshes southern Iraq during the period from January to December 2011, by Plankton net of a mouth aperture of 40 cm and a mesh-size 0.90 mm mounted with a flow meter in the mouth. The results showed that the population density of Cladocera ranged between 79 ind/m3 during winter at station 1 (Al-Mas-hab) and 41971 ind/m3 during spring at station 2 (Hareer). Density of Cladocera was positively correlated with water temperature and to a lesser extent with salinity. About 13 species of Cladocera belonging to 11 genera were recorded at three stations. The high values ​​of diversity were recorded in winter at all stations (1.68, 1.16, and 1.68 respectively) while the lowest values were recorded during spring at all stations (0.06, 0.03, and 0.01 respectively).